-2x-4x=-3(-4x-6)+6(7-8x)

Simple and best practice solution for -2x-4x=-3(-4x-6)+6(7-8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-4x=-3(-4x-6)+6(7-8x) equation:


Simplifying
-2x + -4x = -3(-4x + -6) + 6(7 + -8x)

Combine like terms: -2x + -4x = -6x
-6x = -3(-4x + -6) + 6(7 + -8x)

Reorder the terms:
-6x = -3(-6 + -4x) + 6(7 + -8x)
-6x = (-6 * -3 + -4x * -3) + 6(7 + -8x)
-6x = (18 + 12x) + 6(7 + -8x)
-6x = 18 + 12x + (7 * 6 + -8x * 6)
-6x = 18 + 12x + (42 + -48x)

Reorder the terms:
-6x = 18 + 42 + 12x + -48x

Combine like terms: 18 + 42 = 60
-6x = 60 + 12x + -48x

Combine like terms: 12x + -48x = -36x
-6x = 60 + -36x

Solving
-6x = 60 + -36x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '36x' to each side of the equation.
-6x + 36x = 60 + -36x + 36x

Combine like terms: -6x + 36x = 30x
30x = 60 + -36x + 36x

Combine like terms: -36x + 36x = 0
30x = 60 + 0
30x = 60

Divide each side by '30'.
x = 2

Simplifying
x = 2

See similar equations:

| v*8=16 | | -15k+9k=36 | | 4x+5/2x=1/2 | | 2z+16=58 | | 3d-4=d+11 | | 2(1.5y+2)=3y+4 | | 16=2x-4x | | -7c+10c=33 | | p+p+81=180 | | 3(t-4)-2(2t+3)=-4 | | 18=-9v | | 21-22= | | 3(x+12)=3x+12 | | 2p+81= | | Y+1.91=8.75 | | 4+6(n)=9(n)+10 | | -6=x-2-8 | | b+3.5=5.21 | | 6.25t=44.25 | | 4(-8x+-5)=-32x-26 | | 5x-6=3x+22 | | 8-7(n)=4+3(n) | | (4/25)^2×2^4(15/2) | | (3x+16)=(11x-18) | | 9p+5=-15 | | Cos(-3.14/4)^2 | | 2p+10-7=4p | | 20x-8=-6+38 | | -23=-8+8r-3r | | 32g-30g=-40 | | 20d-25d=-50 | | 4.9x-1.9=27.57 |

Equations solver categories